Satisfacción con la enseñanza en odontología según los niveles de estudios de la Universidad Nacional de la Amazonia Peruana - Flores Marin, Alan Eduardo (2024)
Objective: To assess satisfaction with dental education according to the levels of study at the National University of the Peruvian Amazon. Method: This study is quantitative, cross-sectional, non-experimental, and prospective. Population: The population will consist of students from the IV, V, and VI levels of study at the School of Dentistry at the National University of the Peruvian Amazon. An estimated population of 132 students is calculated. Results: 5% (6 people): Rate their satisfaction with teaching performance as poor. 14% (19 people): Consider their satisfaction to be fair. 40% (53 people): Believe their satisfaction with teaching performance is good. 32% (42 people): Rate it as very good. 9% (12 people): Consider it excellent. Conclusion: The overall quality of teaching in the dentistry program is perceived predominantly positively by students, with a large majority rating it as "good" or "very good." However, there are areas for improvement, such as the clarity of course objectives and the accessibility of professors, which, although also positively valued, show some areas of dissatisfaction that could be optimized.